Relasi Sipil-Militer dalam Pemberdayaan Masyarakat Papua - Tippe, Syafrudin (Masyarakat: Jurnal Sosiologi, 2014)
This research attempts to show that active role of agencies allows an adequate civil–military relation to be established despite of some constrains to the relationship between the two. Employing qualitative approach to assess civil–military cooperation in empowering Papuan society, the case study shows how the military and civilian collaborated to subdue the social tension in a territory prone to conflict. The result suggests that military component took pivotal role in maintaining peace and national security in Papua. Through its history, Indonesian government planned Papua development with military’s involvement on one side, yet without any attempt to embrace the subject of that development itself on the other. This expectedly gave rise to the dispute between military and civilian. However, civil–military cooperation in empowering indigenous Papuan based on local culture and local people initiative proven to be effective in reducing the risk of conflict, in addition to being a case of how the role of agencies could be vital in the making of a better condition.